2005
DOI: 10.1073/pnas.0501881102
|View full text |Cite
|
Sign up to set email alerts
|

Glutamate induces the rapid formation of spine head protrusions in hippocampal slice cultures

Abstract: Synaptic plasticity at neuronal connections has been well characterized functionally by using electrophysiological approaches, but the structural basis for this phenomenon remains controversial. We have studied the dynamic interactions between presynaptic and postsynaptic structures labeled with FM 4-64 and a membranetargeted GFP, respectively, in hippocampal slices. Under conditions of reduced neuronal activity (1 M tetrodotoxin), we observed extension of glutamate receptor-dependent processes from dendritic … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

15
127
0

Year Published

2006
2006
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 153 publications
(142 citation statements)
references
References 29 publications
15
127
0
Order By: Relevance
“…Although dendritic spine plasticity and synaptic AMPA receptor plasticity have been shown to be highly correlated in a number of studies (McKinney et al, 1999;Matsuzaki et al, 2004;Richards et al, 2005;Okamoto et al, 2009), other studies have found that changes in spine morphology and synaptic AMPA receptors can be differentially mediated (Sdrulla and Linden, 2007;Wang et al, 2007). Until the present study, it has not been known whether these two cellular processes can be differentially mediated in drug-induced plasticity of excitatory synapses.…”
Section: Introductionmentioning
confidence: 40%
“…Although dendritic spine plasticity and synaptic AMPA receptor plasticity have been shown to be highly correlated in a number of studies (McKinney et al, 1999;Matsuzaki et al, 2004;Richards et al, 2005;Okamoto et al, 2009), other studies have found that changes in spine morphology and synaptic AMPA receptors can be differentially mediated (Sdrulla and Linden, 2007;Wang et al, 2007). Until the present study, it has not been known whether these two cellular processes can be differentially mediated in drug-induced plasticity of excitatory synapses.…”
Section: Introductionmentioning
confidence: 40%
“…For example, glutamate stabilizes spines when spontaneously released from presynaptic terminals (McKinney et al, 1999) and causes the formation of small protrusions from the spine head when focally applied (Richards et al, 2005). Glutamate signaling through AMPA receptors is known to stabilize the actin cytoskeleton and spine motility (Fischer et al, 2000).…”
Section: Discussionmentioning
confidence: 99%
“…Changes in neuronal activity have been proposed to influence protrusion size and dynamics (Dunaevsky et al, 1999;Fischer et al, 2000;Nimchinsky et al, 2002;Richards et al, 2005; Zuo et al, 2005a,b). The rapid translocation of paralemmin-1 to the plasma membrane upon stimulation of neuronal activity prompted us to examine whether paralemmin-1 modulates activity-driven changes in dendritic protrusions.…”
Section: Paralemmin-1 Potentiates Activity-driven Membrane Expansionmentioning
confidence: 99%
“…Neuronal activity modulates protrusion formation, which in turn fine tunes synaptic strength and plasticity (Dunaevsky et al, 1999;Fischer et al, 2000;Nimchinsky et al, 2002;Richards et al, 2005;Zuo et al, 2005a,b). This process is thought to be mediated by the recruitment of proteins that alter membrane and cytoskeletal dynamics.…”
Section: Neuronal Activity Enhances Membrane Localization Of Paralemmmentioning
confidence: 99%